1992
DOI: 10.1577/1548-8667(1992)004<0143:aoshai>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Shrimp Hemolymph and Ionic Modification of aPenaeusCell Culture Formulation

Abstract: The levels of 19 constituents of penaeid shrimp hemolymph were analytically determined. Ionic components of hemolymph were influenced by water salinity but not by water pH or temperature. Levels of hemolymph metabolites varied from sample to sample; the differences were possibly generated by variations in diet and stress. Enzymatic measurements were reported for possible comparison with future studies on stress, health, or immune status of cultured penaeid popula-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…To date, a medium exclusively for in vitro growth of shrimp cell cultures has not been designed, and the fact that an appropriate medium is required to establish shrimp cell lines in tune with the quantum change which the Grace's insect cell culture medium [29][30][31][32] has brought about; ever since the publication of Grace's insect cell culture medium, over 500 insect cell lines could be established [53,76]. Likewise, to formulate an exclusive shrimp cell culture medium, indepth analysis of the biochemistry of body fluids [64,74] is the prime requirement. Moreover, to tide over the difficulties in developing a complete medium for shrimp cell culture, attention must be directed towards satisfying the nutritional requirements of each cell type.…”
Section: Cell Culture Medium: a Stepping Stone For Cell Line Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, a medium exclusively for in vitro growth of shrimp cell cultures has not been designed, and the fact that an appropriate medium is required to establish shrimp cell lines in tune with the quantum change which the Grace's insect cell culture medium [29][30][31][32] has brought about; ever since the publication of Grace's insect cell culture medium, over 500 insect cell lines could be established [53,76]. Likewise, to formulate an exclusive shrimp cell culture medium, indepth analysis of the biochemistry of body fluids [64,74] is the prime requirement. Moreover, to tide over the difficulties in developing a complete medium for shrimp cell culture, attention must be directed towards satisfying the nutritional requirements of each cell type.…”
Section: Cell Culture Medium: a Stepping Stone For Cell Line Developmentmentioning
confidence: 99%
“…Moreover, six authors (16 %) selected Penaeus stylirostris [49,51,63,73,74,78] as the donor animal of tissues and organs. Besides, in two publications (4 %) Penaeus indicus [46,82] and Penaeus aztecus [18,64] were the species used. There is only one report (2 %) of using P. penicillatus [10] for extracting tissues and organs for cell culture development (Fig.…”
Section: Species Of Choice: a Major Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…As the analysis of major ions in the hemolymph is crucial to formulate cell culture medium (Najafabadi et al 1992), metal ion strength of haemolymph and seawater at 27 % salinity were analyzed using Inductively Coupled Plasma Atomic Emission Spectrometer (ICP-AES Thermo Electron IRIS INTREPID II XSP DUO). Before analysis, seawater was sterilized by autoclaving at 15 lbs for 15 min, filtered through Whatman No.…”
Section: Analysis Of Metal Ionsmentioning
confidence: 99%
“…Mulford et al (2001) revealed that 2 9 Leibovitz's medium supplemented with 10 % (v/v) heat inactivated FBS, 5 % (v/v) muscle extract, 0.06 g l -1 of L-proline, 1 g l -1 glucose prepared in 25 % seawater was effective for cell migration, survival and longevity. Though the hemolymph composition of P. aztecus and P. stylirostris had been reported earlier (Najafabadi et al 1992;Shimizu et al 2001), a medium exclusively for shrimp cell culture based on it could not be attained so far, other than the modification of the existing media. This might be cited as one of the reasons for the non attainment of immortal cell line from shrimp.…”
Section: Introductionmentioning
confidence: 99%